2008
DOI: 10.1016/s0377-1237(08)80005-6
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Haemoglobinopathies in a Tertiary Care Hospital of Armed Forces

Abstract: This study provides a comprehensive database on the spectrum of haemoglobinopathies in the Armed Forces. It is suggested that detection of HbA2 should be carried out in all the high-risk groups with anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…The frequency of thalassaemia is increased by consanguity & endogenous mating , it may be assumed that tribal community in India are facing the problem at large scale. 9 Chopra et al 10 This study provides a data on spectrum of haemoglobinopathy in rural based tertiary care hospital (Index Medical Collage & Hospital) for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of thalassaemia is increased by consanguity & endogenous mating , it may be assumed that tribal community in India are facing the problem at large scale. 9 Chopra et al 10 This study provides a data on spectrum of haemoglobinopathy in rural based tertiary care hospital (Index Medical Collage & Hospital) for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…The mean MCH among carriers of hemoglobinopathies was significantly lower than normal cases in the study. A low MCH and a low MCV predicts the presence of thalassemia [9].…”
Section: Discussionmentioning
confidence: 99%
“…18 Chopra et al revealed that out of 1032 participant, 258 (25%) cases had abnormal hemoglobin. 19 The issue of hemoglobinopathies in India is aggravated by the diversity of population. The gene frequency for various hemoglobinopathies varies across different regions of India.…”
Section: Discussionmentioning
confidence: 99%